2015
DOI: 10.18632/oncotarget.6230
|View full text |Cite
|
Sign up to set email alerts
|

Transcription factor LSF (TFCP2) inhibits melanoma growth

Abstract: ABSTRACT

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

0
20
1

Year Published

2016
2016
2022
2022

Publication Types

Select...
8

Relationship

0
8

Authors

Journals

citations
Cited by 26 publications
(21 citation statements)
references
References 22 publications
0
20
1
Order By: Relevance
“…Moreover, several studies have shown that CDKN1A plays a crucial role in cancer cells by modulating cell cycle arrest, cell growth, proliferation, migration inhibition, and apoptosis induction (Abbas and Dutta, 2009). Goto et al (2016) found that TFCP2 plays a predominant role in the regulation of CDKN1A, thereby inhibiting cell growth. In our study, CDKN1A expression was significantly upregulated when miR-660-5p was inhibited.…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…Moreover, several studies have shown that CDKN1A plays a crucial role in cancer cells by modulating cell cycle arrest, cell growth, proliferation, migration inhibition, and apoptosis induction (Abbas and Dutta, 2009). Goto et al (2016) found that TFCP2 plays a predominant role in the regulation of CDKN1A, thereby inhibiting cell growth. In our study, CDKN1A expression was significantly upregulated when miR-660-5p was inhibited.…”
Section: Discussionmentioning
confidence: 99%
“…TFCP2 functions as an oncogene in hepatocellular carcinomas, and an increased expression level of TFCP2 promotes malignant progression (Saxena et al, 2010). Goto et al (2016) found an opposite role of TFCP2 in melanoma, whereby increased TFCP2 expression levels suppressed both the anchorage-dependent and -independent growth of melanoma cells. However, the functions and the specific molecular mechanism of action of TFCP2 in breast cancer remain obscure.…”
Section: Introductionmentioning
confidence: 99%
“…cluster that has been shown to be involved in many cellular functions, including cell proliferation, migration and differentiation. [13][14][15] The miR-23b/24/27b cluster can act as a tumor suppressor in prostate, ovarian, bladder and colorectal cancers, 3,[16][17][18] whereas it promotes tumor progression in breast cancer. 19 However, the role of miR-23b in normal tissue, including epidermis, remains to be clarified.…”
Section: Mir-23b Belongs To the Mir-23b/24/27bmentioning
confidence: 99%
“…However, the expression level of TFCP2 is decreased in melanoma, and up‐regulated TFCP2 suppresses melanoma cell growth and increases the percentage of G1 phase cells (Goto et al . ).…”
Section: Discussionmentioning
confidence: 97%
“…Inhibition of TFCP2 abrogates HCC cell growth and metastasis in vivo and in vitro (Santhekadur et al 2012;Rajasekaran et al 2015). However, the expression level of TFCP2 is decreased in melanoma, and up-regulated TFCP2 suppresses melanoma cell growth and increases the percentage of G1 phase cells (Goto et al 2016).…”
Section: Discussionmentioning
confidence: 99%